Emission computed tomography test phantoms: a review - Sayed, Raheela Bibi; Sayed, Inayatullah Shah; Abdul Rahim, Mohamad Shahrir (2019)
It is vital to assess the performance of emission computed tomography (ECT) systems prior to their use for clinical examinations. Generally, performance tests of ECT systems are time-consuming, expensive and require more than one phantom to scan and then analyse the data. There is non-availability of such type of phantoms that can provide all necessary data for performance of some quality control (QC) tests from a single scan data. In this paper, commercially available emission computed tomography (ECT) phantoms are thoroughly reviewed. Thus,designing and construction of a time-saving and cost-effective new compact ECT phantom has been suggested.